Analisis Gaya Belajar Mahasiswa Pada Mata Kuliah Kajian Pedagogik - Nofriansyah Nofriansyah; Nani Sutarni; Edutivia Mardetini; Sugeng Riyadi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
This study examines the learning styles of Postgraduate Doctoral Students in Economic Education at the Indonesia University of Education. The purpose of this study was to describe the learning styles of students of the Doctoral Programme in Economic Education at the Indonesia University of Education. This research method is Classroom Action Research (PTK. The population and research sample totalled 15 people. The sampling technique used in the study was saturated sampling. The data collection technique is a questionnaire. Based on the results of the questionnaire of 15 people who filled out the questionnaire, it is known that 7 Doctoral students use a visual learning style, 5 Doctoral students use an auditory learning style, and 3 Doctoral students use a kinesthetic learning style. Therefore, it is concluded that the most commonly used learning style among Postgraduate Students of Economic Education in Pedagogical Studies courses at the Indonesia University of Education is the visual learning style